The Influence Of Organizational Culture, The Attitude Of The Lecturer Toward Women’s Leadership, And Job Satisfaction On Organizational Commitment In The ‘Aisyiyah University Yogyakarta - Rufaida Setyawati; Ma'ruf Akbar; Muchlis R. Luddin (Fakultas Ekonomi, Universitas Negeri Jakarta, 2020)
The research is conduted to find the relationship between organizational culture, ob statistifaction, and the attitude of lecturers who were not serving in leadership, both structural and functional positions toward women’s leadership on organizational commitment in ‘Aisyiyah University (UNISA) Yogyakarta. The population of the research was 153 people, then the number of samples was determined by following the Slovin formula and obtained 111 respondents. Samples used as respondents from each faculty and study program were determined randomly. so the sampling technique is included in the category of random sampling. The research method uses a quantitative approach with survey data collection methods, and uses path analysis techniques. The findings of this research are 1) there is a positive direct effect of organizational culture on organizational commitment, 2) there is a direct negative effect on organizational culture on job satisfaction, 3) there is a positive direct effect of attitudes on women's leadership on job satisfaction, 4) there is a positive direct effect of organizational culture on organizational commitment, 5) there is a positive direct effect of attitudes on women's leadership on organizational commitment, 6) there is a direct positive direct effect on job satisfaction on organizational commitment, 7) there is an indirect direct negative effect on women's organizational culture on organizational commitment through job satisfaction, 8) there is a direct indirect effect of positive attitudes towards women's leadership on organizational commitment through job satisfaction.